Bargaining towards maximized resource utilization in video streaming datacenters - Yuan Feng; Baochun Li; Bo Li (2012 Proceedings IEEE INFOCOM, 2012)
Datacenters can be used to host large-scale video streaming services with better operational efficiency, as the multiplexing achieved by virtualization technologies allows different videos to share resources at the same physical server. Live migration of videos from servers that are overloaded to those that are under-utilized may be a solution to handle a flash crowd of requests, in the form of virtual machines (VMs). However, such migration has to be performed with a well-designed mechanism to fully utilize available resources in all three resource dimensions: storage, bandwidth and CPU cycles. In this paper, we show why the challenge of maximizing resource utilization in a video streaming datacenter is equivalent to maximizing the joint profit in the context of Nash bargaining solutions, by defining utility functions properly. Having servers participating as players to bargain with each other, and VMs as commodities in the game, trades conducted after bargaining govern VM migration decisions in each server. With extensive simulations driven by real-world traces from UUSee Inc., we show that our new VM migration algorithm based on such Nash bargaining solutions increases both the resource utilization ratio and the number of video streaming requests handled by the datacenter, yet achievable in a lightweight fashion.